2022
DOI: 10.1021/acs.jpcb.2c06530
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphate on Network Connectivity and Glass Transition in Highly Polymerized Aluminosilicate Glasses

Abstract: Melt-derived metaluminous (Al/Na = 1) aluminosilicate glasses in the system SiO 2 −Al 2 O 3 −Na 2 O−P 2 O 5 were prepared with P 2 O 5 and SiO 2 contents varying from 0 to 7.5 and 50 to 70 mol %, respectively. The glass structure was investigated by X-ray absorption near edge structure, far-and medium-infrared, and polarized Raman spectroscopic techniques. The results indicate the incorporation of phosphate into the aluminosilicate network not only as partially depolymerized groups but also as fully polymerize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 128 publications
0
18
0
Order By: Relevance
“…17 In previous studies, we found the presence of phosphate to reduce glass transition temperature and elastic moduli, owing to decreases in polymerisation and packing density. 18,19 Additionally, our previous structural analysis by Raman and NMR spectroscopy supports the presence of Al–O–P bonds. 19,20 In the literature, the formation of these bonds has been correlated with a change in refractive index in high-silica (>77 mol% SiO 2 ) SiO 2 –Al 2 O 3 –P 2 O 5 glasses.…”
Section: Introductionmentioning
confidence: 56%
See 4 more Smart Citations
“…17 In previous studies, we found the presence of phosphate to reduce glass transition temperature and elastic moduli, owing to decreases in polymerisation and packing density. 18,19 Additionally, our previous structural analysis by Raman and NMR spectroscopy supports the presence of Al–O–P bonds. 19,20 In the literature, the formation of these bonds has been correlated with a change in refractive index in high-silica (>77 mol% SiO 2 ) SiO 2 –Al 2 O 3 –P 2 O 5 glasses.…”
Section: Introductionmentioning
confidence: 56%
“…18,19 Additionally, our previous structural analysis by Raman and NMR spectroscopy supports the presence of Al–O–P bonds. 19,20 In the literature, the formation of these bonds has been correlated with a change in refractive index in high-silica (>77 mol% SiO 2 ) SiO 2 –Al 2 O 3 –P 2 O 5 glasses. 21 The relationship between phosphate content and refractive index in lower silica content sodium aluminosilicate glasses still requires investigation.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations